A comparative study between responses of isolated bovine and equine digital arteries to vasoactive mediators. Issue 1 (13th July 2017) - Zizzadoro, C.; Caruso, M.; Punzi, S.; Crescenzo, G.; Zongoli, F.; Belloli, C.
Abstract : Hemodynamic perturbations, partly resulting from abnormal vasoconstriction of digital vessels, have been implicated in the pathogenesis of bovine and equine laminitis. This study compared the responsiveness of isolated bovine (BDA) and equine (EDA) digital arteries to pharmacological agents that stimulate receptor systems involved in the regulation of normal vessel tone. The role of the endothelium and the short‐ and longer‐term effects of an experimentally induced endothelial damage were also evaluated. Species‐related differences were found in the vessel reactivity to all of the receptor agonists tested. In intact BDA, as compared to intact EDA, norepinephrine was a more effective vasoconstrictor, 5‐hydroxytryptamine a more effective but less potent vasoconstrictor, isoproterenol a less effective vasodilator and carbamylcholine a less potent vasodilator. In BDA, but not in EDA, the contractile responses to norepinephrine and 5‐hydroxytryptamine were enhanced immediately after endothelium removal. However, the contractile reactivity of denuded BDA returned to basal values following overnight incubation. The differences suggest species specificity for the pathophysiology of digital vasomotor tone and function in horses and cattle.